A Mechanism Investigation of how the Alloying Effect Improves the Photocatalytic Nitrate Reduction Activity of Bismuth Oxyhalide Nanosheets. Issue 2 (15th October 2019) - Wang, Liyan; Guo, Sheng‐qi; Chen, Yantao; Pan, Meilan; Ang, Edison Huixiang; Yuan, Zhi‐hao
Abstract: Alloyed bismuth oxyhalides have been widely used in photocatalytic water treatment processes due to their superior photocatalytic activity. However, there is no report on the removal of NO3 − for alloyed bismuth oxyhalides, and the mechanism of the effect of alloying on NO3 − reduction activity is still unclear. In this work, we prepared a series of BiOCln Br1‐n (0≤n≤1) with different Cl/Br ratios but with controlled similar morphologies, and explored their catalytic activities on reducing NO3 − under visible light irradiation. Density functional theory investigations revealed that the formation energy for an oxygen (O) vacancy on the surface of BiOCln Br1‐n alloys is clearly reduced in comparison with the monohalide, illustrating that more O vacancies can be produced on the surface of BiOCln Br1‐n alloys. A high concentration of O vacancies not only promotes the adsorption of NO3 − but also enhances the separation efficiency of the photogenerated electron‐hole (e–h) pairs, with both being beneficial to enhance the photocatalytic activity of BiOCln Br1‐n alloys for NO3 − reduction. These new discoveries not only promote the design and development of new photocatalysts with excellent NO3 − reduction properties, but also help to understand the relationship between alloying effects and semiconductor photocatalytic properties. Abstract : Room to manoeuvre : A series of BiOCl n Br1‐ n (0≤n≤1) nanosheets with different Cl/Br ratios were prepared. It was confirmed that the alloying effect could reduce the formation energy of O vacancies on the surface of BiOCl n Br1‐ n alloys. O vacancy formation not only promotes the adsorption of NO3 −, but also improves the separation ability of photogenerated electron‐hole pairs, both of which being beneficial to enhance the photocatalytic activity of BiOCl n Br1‐ n alloys for NO3 − reduction.